Transforming Healthcare Through Telemedicine: A Post-Pandemic Perspective - Akram, Muhammad; Umaru, Isaac John; Mahmood, Abid; Hasan, Mohammed Khudhair; Abdulghafoor, Hind A.; Khan, Fahad Said; Ozdemir, Fethi Ahmet; Sołowski, Gaweł; Ali, Jaouher Ben (African Journal of Clinical Medicine and Pharmacy Research, 2025)
The global chaos caused by COVID-19 gave birth to emerging telemedicine innovations throughout the world. Telemedicine automates the diagnosis and therapy processes as well as provides care to aid in such physically demanding tasks. In today's world, telemedicine is becoming one of the most effective methods of assisting patients directly due to its easily accessible reach and practicality. This paper concentrates on the epidemiology of telemedicine, along with the diverse services prescribed by the doctors through telecommunication, as well as the prevailing global communications and access problems.